Renal Dysfunction Is an Independent Risk Factor for Poor Outcome in Acute Ischemic Stroke Patients Treated with Intravenous Thrombolysis: A New Cutoff Value - Elyar Sadeghi-Hokmabadi; Demet Funda Baş; Mehdi Farhoudi; Aliakbar Taheraghdam; Daryoush Savadi Oskouei; Mohammad Yazdchi; Maziyar Hashemilar; Nevzat Uzuner; Reshad Mirnour; Ertugrul Colak; Atilla Özcan Özdemir (Stroke Research and Treatment)
Objective. This study was set to assess the effect of renal dysfunction on outcome of stroke patients treated with intravenous thrombolysis (IVT). Methods. This multicenter research involved 403 patients from January 2009 to March 2015. Patients were divided into two groups: (1) control group with GFR ≥ 45 mL/min/1.73 m2 and (2) low GFR group with GFR < 45 mL/min/1.73 m2. Outcome measurements were poor outcome (mRS 3–6) and mortality at 3 months and symptomatic intracerebral hemorrhage (SICH) within the first 24–36 hours. Univariate and multivariate regression analyses were performed, and odds ratios (ORs) were determined at 95% confidence intervals (CIs). Results. Univariate analyses determined that every decrease of GFR by 10 mL/min/1.73 m2 significantly increased the risk of poor outcome (OR 1.19, 95% CI 1.09–1.30, p<0.001) and mortality (OR 1.18, 95% CI 1.06–1.32, p=0.002). In multivariate regression, adjusted for all variables with p value < 0.1, low GFR (GFR < 45 versus GFR equal to or more than 45) was associated with poor outcome (OR adjusted 2.15, 95% CI 1.01–4.56, p=0.045). Conclusion. In IVT for acute stroke, renal dysfunction with GFR < 45 mL/min/1.73 m2 before treatment determined increased odds for poor outcome compared to GFR of more than 45 mL/min/1.73 m2.